2006
DOI: 10.1186/cc5124
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction Established fluid treatment formulas for burn injuries have been challenged as studies have shown the presence of tissue hypoxia during standard resuscitation. Such findings suggest monitoring at the tissue level. This study was performed in patients with major burn injuries to evaluate the microdialysis technique for the continuous assessment of skin metabolic changes during fluid resuscitation and up to four days postburn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 44 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Despite the fact that insulin levels are lower in peripheral tissues, such as the skin, our results indicate that it has an active local role in maintaining local metabolic homeostasis as well as having an effect on the local microcirculation. Previous studies using microdialysis in the skin, for example in burn patients 27 and in reconstructive surgery 28 , show local effects in the skin that may not be seen in the central circulation, suggesting an un-coupling effect between local tissue homeostasis and central vital functions. Therefore, a better understanding of the connection between local impaired glucose metabolism and ischemia is essential to finding ways to prevent morbidity, and the need for further surgery when the skin homeostasis is challenged.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the fact that insulin levels are lower in peripheral tissues, such as the skin, our results indicate that it has an active local role in maintaining local metabolic homeostasis as well as having an effect on the local microcirculation. Previous studies using microdialysis in the skin, for example in burn patients 27 and in reconstructive surgery 28 , show local effects in the skin that may not be seen in the central circulation, suggesting an un-coupling effect between local tissue homeostasis and central vital functions. Therefore, a better understanding of the connection between local impaired glucose metabolism and ischemia is essential to finding ways to prevent morbidity, and the need for further surgery when the skin homeostasis is challenged.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research on how the expression of these proteins is affected by a glucose provocation is limited, although the connection between especially angiotensinogen and kininogen-1 is well known in relation to microcirculatory processes and effects on blood flow related to activation of the nitric oxide pathway. An improved understanding of what biological processes occur in skin and subcutaneous tissue, secondary to increased systemic insulin levels, is likely to be of importance for targeted treatments where glucose delivery to the target tissue is hampered as a result of serious illness and deranged glucose-insulin functions 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Only the unbound concentration in the interstitium, however, is considered to contribute to the efficacy of anti-infectives. Similarly, a moderate correlation or a lack or correlation has been observed between serum and tissue cortisol levels in sepsis or burn injury [ 23 , 30 ]. From a pathophysiological point of view the equilibrium between plasma and tissue interstitial space in the setting of sepsis may be incomplete due to interstitial edema, impairment of the microcirculation or administration of vasopressor agents [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, monitoring of the interstitium is feasible with the implementation of minimally invasive techniques, including microdialysis (MD) [ 15 , 16 , 17 , 18 ]. MD is now increasingly used in critically ill septic patients as a research tool and the measurement of metabolites, such as lactate, pyruvate and glycerol together with the calculation of the lactate/pyruvate (L/P) ratio, directly assess energy metabolic disorders at the tissue level [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. In this regard, a recent study by our group examined the interplay between adipose tissue and blood lactate and found that in ICU patients with septic or cardiogenic shock the rise in tissue lactate preceded the increase in blood lactate [ 19 ].…”
Section: Introductionmentioning
confidence: 99%